ANALISIS PERBANDINGAN PENGGUNAAN JARINGAN 4G DENGAN 5G MENGGUNAKAN APLIKASI OPENSIGNAL DI AREA URBAN KOTA MAKASSAR - Saktiani Karim; Nursin; Faridah Faridah; Sriwati Sriwati (Fakultas Teknik Universitas Islam Makassar, 2026)
The development of cellular technology from 4G to 5G provides significant improvements in network speed and capacity, especially in urban areas with high data needs. This study aims to analyze and compare the performance of 4G and 5G networks in urban areas using the OpenSignal application with download, upload, and latency speed parameters. The research method uses a quantitative approach through field measurements conducted on May 25–June 2, 2025, in the morning, afternoon, and evening. The results show that the average download and upload speeds of the 5G network are 55.26 Mbps and 19.6 Mbps, respectively, higher than 4G which only reaches 13.18 Mbps and 9.83 Mbps. The difference in download speed reaches 31.92%, while in upload speed it is 9.93%. However, 4G latency is lower with a difference of 18.9% compared to 5G. Overall, the 5G network has superior and stable performance, making it ideal for activities with large bandwidth requirements. This is also influenced by infrastructure factors, user density, and distance to BTS which can cause performance variations between times and locations.